New and poorly known giant scale insects (Homoptera: Coccinea: Margarodidae s. lat.) from the Oriental region with taxonomic and nomenclatural notes on the subfamily Monophlebinae - Gavrilov-Zimin, Ilya A. (European Journal of Taxonomy, 2021)
A new scale insect genus and species, Gompholopium quercicola gen. et sp. nov. is described and illustrated, based on material from China (Yunnan Prov.). Hemaspidoproctus cinereus (Green, 1922) is redescribed, based on material from India (Allahabad). Walkeriana tosariensis Reyne, 1957 is transferred to the genus Hemaspidoproctus Morrison, 1927 – H. tosariensis (Reyne, 1957) comb. nov. Monophlebus neglectus Gavrilov-Zimin, 2018 syn. nov. is formally synonymized with the unrecognizable Monophlebus atripennis Burmeister, 1835 in order to resolve an old taxonomic and nomenclatural problem in the subfamily Monophlebinae.